Research of indicators of sustainable development in the field of healthcare management (BASED ON MATERIALS FROM THE REGIONS OF THE REPUBLIC OF KAZAKHSTAN) - Aygul Tulemetova; Maksat Yelikbay; Aygyl Tulemetova; Madina Sergazieva; Aizharkyn Sadykbekova; Gulzhamal Koptyaeva (Qubahan Academic Journal)
Achieving Sustainable Development Goal 3 is a complex and challenging task. The main obstacles to achieving the goal are: inadequate health financing, health inequalities, communicable diseases and pandemics, non-communicable diseases, complexity of health services. The importance of health as a systemically important factor in economic development, both nationally and globally, is undeniable. The long term development of health care involves the creation of efficient, affordable and environmentally sound systems that provide good quality of life in health services and improve the quality of life. The aim of this study is to show that in order to achieve a sustainable transition to sustainable health care, a multidisciplinary approach involving partnerships between public entities, the private sector and civil society is necessary. This co-operation will create the conditions for a more sustainable, accessible and efficient health care system capable of responding to contemporary challenges and maintaining global health. The study is devoted to the substantiation of an integrated conceptual approach to the study of the health care system. The methodological basis of the study is represented by a set of provisions on sustainable socio-economic development, the theory of systems sustainability, as well as concepts of health care development. The article analyses the state of the health care system in the Republic of Kazakhstan. The current state of the health care system is assessed, the trends in the development of the health care system are identified and shown. The group of health care sustainability indicators is generalised. The key conclusions about the fundamental indicators are made and the basic factors of increasing the sustainable development of the health care sphere are determined. The novelty of the study is related to the sustainable development of the health care sector and consists in an integrated approach to the analysis and development of strategies aimed at long-term improvement of the quality and availability of health care services, taking into account environmental, economic and social aspects.